PENGARUH KEPEMIMPINAN DAN DESKRIPSI PEKERJAAN TERHADAP PENGEMBANGAN KARIR DAN DAMPAKNYA TERHADAP SEMANGAT KERJA PEGAWAI SEKRETARIAT DAERAH KABUPATEN SIAK (Jurnal Tepak Manajemen Bisnis, 2014)
This study aims to determine the direct influence of leadership and job descriptions on career development, thedirect and indirect influence of leadership and job description on morale through career development and directinfluence of career development on morale. The study population was all employees who work on the SiakDistrict Secretariat totaling 184 people. The samples in this study were employees who elected with use Slovinformula as many as 126 people. The instrument used for data collection was a questionnaire with Likert scalemodels. To test the hypothesis used descriptive analysis and path analysis.Results of data analysis showed that the seventh hypothesis is acceptable at 95% confidence level. It wasconcluded that the direct influence Morale Leadership by 5.9%, directly affect Job Description Morale of 3.9%,Career Development directly affects 18.2% Morale, Leadership directly affects 9.9% of Career Development, JobDescription directly affect 26.8% of Career Development, Leadership Morale affects indirectly through theCareer Development of 53.5%, and the Job Description Morale affects indirectly through the Career Developmentof 46.5%.Keywords: Leadership, Job Description, Career Development and Morale.